ANALISIS LAMBUNG KERANG BAKAU (Polymesoda bengalensis Lamarck.) DI MUARA NIPAH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - putri, Dinelia Sari; Widiana, Rina; Lusi Zeswita, Armein (Pendidikan Biologi, 2014)
ABSTRACBivalve is one of fisheries products having essential value as a source of food.  It is caught in a variety of type sand sizes. Polymesoda bengalensis is a regarded as filtration feeders and detritus feeders. Filtration feeders refine plankton from the waters around, while the Detritus feeders make use of organic materials from plants falling down to the bottom of the water. This research was   designed for revealing the natural forage given to the cultivation of Polymesoda bengalensis. This cresearch was conduced in January 2013 to analyze Polymesoda bengalensis bowel in Muara Nipah Kecamatan Sutera Kabupaten Pesisir Selatan. To conduct the research, survey Descriptive method was applied. The sample was was chosen by using Random Sampling method. The numbers of the sample analyzed was 30 in which the length of the bivalves bodies were < 30 mm, 30-50 mm, and > 50 mm. There were 10 bivalves taken as the representation of each size.Based on the result of data analysis, Detritus and 12 genus of Phytoplankton were found in the Polymesoda bengalensis bowel. Detritus was the most dominant natural forage found in the bivalves bowel. The frequency of its existence was 100%.   In the bowel of bivalves of <30 mm length, Detritus was the most dominant food found (49,465) followed by Synedra (8,6%). In the bowel of bivalves of 30-50 mm length, the food found was dominated by Detritus (47,77%) followed by Synedra (10%), while in the bowel of bivalves of > 50 mm length, the food found was dominated by Detritus (39,13%) follwed by Cymbella (10,43%). Based on the preference viewed from the Largest Index, the natural forage for the bivalve of < 30 mm length, Oedogonium and Detritus were considered as the main food, meanwhile, for the bivalve of > 50 mm length, Detritus was as the main food. Based on the result of data analysis, it was revealed that the main forage for Polymesoda bengalensis was Detritus and Oedogonium.